Solving the travelling salesman problem by using artificial bee colony algorithm / Noor Ainul Hayati Mohd Naziri - Mohd Naziri, Noor Ainul Hayati (2021)
Travelling Salesman Problem (TSP) is defined as a list of cities that must visit all cities that start and end in the same city with the aim of finding the minimum cost of time or distance. In this study, the Artificial Bee Colony (ABC) algorithm was used to resolve the TSP. ABC algorithms is an optimisation technique that simulates the foraging behaviour of honey bees and has been successfully applied to various practical issues. ABC algorithm has three types of bees that are used by bees, onlooker bees, and scout bees. In Bavaria from Library of Traveling Salesman Problem with the distance from a city to another city has been used to find the best solution of the shortest distance. The result shows that the best solution for the shortest distance that traveller have to travel all the 29 cities in Bavaria is 3974km.